PENGARUH PEMBERIAN AIR REBUSAN DAUN SALAM TERHADAP PENURUNAN KADAR ASAM URAT PADA PENDERITA GOUT ARTHRITIS DI WILAYAH KERJA PUSKESMAS RAMBAH SAMO II TAHUN 2023 - Yuyun Priwahyuni; Diva Sukma Rani; Nurhapipa Nurhapipa; Christine Vita Gloria Purba; Nurvi Susanti (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
The prevalence of gout in Riau Province is around 7%. Puskesmas Rambah Samo II was one of the health centers with a relatively high prevalence of gout arthritis. According to the data from Puskesmas Rambah Samo II, gout arthritis was one of the top three diseases in the health center. The prevalence of gout arthritis increased, from 222 cases (1.84%) in 2021 to 348 cases (2.89%) in 2022.The aim of this study was to determine the effect of boiled bay leaf water on reducing uric acid levels in patients with gout arthritis in the working area of Puskesmas Rambah Samo II in 2023. This study used the Quasi-Experimental research method with a Nonequivalent Control Group design. The population consisted of 348 patients with gout arthritis, with a sample size of 62 patients, divided into 31 control group and 31 experimental group. Purposive sampling technique was used for sample selection. The analysis used was the Wilcoxon test. The results of the study showed that there was an effect of boiled bay leaf water on reducing uric acid levels in the experimental group with a ρ value (0.000) <0.05, while the control group did not show a decrease in uric acid levels with a ρ value (0.244) >0.05. It was hoped that the results of this study could be considered as an alternative for reducing uric acid levels.